Carbon quantum dots/hydrogenated TiO2 nanobelt heterostructures and their broad spectrum photocatalytic properties under UV, visible, and near-infrared irradiation. (January 2015) - Tian, Jian; Leng, Yanhua; Zhao, Zhenhuan; Xia, Yang; Sang, Yuanhua; Hao, Pin; Zhan, Jie; Li, Meicheng; Liu, Hong
Abstract: To make the best and highest use of solar light is the main direction and object of photocatalysis and water-splitting. Although UV and visible active photocatalysts have been extensively investigated, the use of near-infrared (NIR) wave band of solar light remains a nearly blank area. Here we report the UV–visible–NIR broad spectrum active photocatalytic property of CQDs/hydrogenated TiO2 (H-TiO2 ) nanobelt heterostructures. The improved UV and visible photocatalytic property can be attributed to improved optical absorption, charge carrier trapping, and hindering of the photogenerated electron–hole recombination of oxygen vacancies and Ti 3+ ions in TiO2 nanobelts created by hydrogenation. The NIR photocatalytic activity is from photo-induced electron transfer, electron reservoir, and up-converted PL properties of CQDs, which can absorb NIR light and convert into visible light and transfer to visible photocatalytic active H-TiO2 nanobelts. This work offers a simple strategy for the fabrication of a wide spectrum of active heterostructured photocatalysts by assembling CQDs on the surface of UV–visible photocatalysts, which opens a door for photodegradation, photocatalytic water splitting, and enhanced solar cells using sunlight as light source. Graphical abstract: Highlights: Utilize solar wide spectrum (UV, visible, and NIR) in photocatalysis for organic contaminants removal and hydrogen fuel production. The up-converted PL properties of CQDs make the H-TiO2 nanobelts have NIR light photocatalytic activity. A 1-D TiO2 nanostructure based heterostructure was designed: CQDs/H-TiO2 heterostructure.